Perbandingan Pengaruh Latihan Fisik Interval Tinggi Dengan Kontinu Terhadap Heart Rate Istirahat, VO2Max Dan Heart Rate Recovery Pada Atlet Renang Pria POR SURYANAGA Surabaya - Fatikhawati, Anandya; Prahasanti, Kartika; Efendi, Choesnan (JOSSAE (Journal of Sport Science and Education), 2021)
Exercise with HICT methods is not the only effort to prevent cardiovascular disease. The development of science and technology of sports has resulted in the latest innovations and discoveries such as High Intensity Interval Training (HIIT) method that can improve cardiovascular abilities. HIIT is more flexible to do than High Intensity Continous Training (HICT) method. The purpose of this study is to compare exercise with HIIT and HICT method. It is an experimental quasy using 32 swimming athletes who were divided into two groups and given different training to measure VO2max, heart rate recovery, and resting heart rate. Subjects did training for five weeks with a frequency of exercise five times a week. The results show an increase in VO2Max in the HIIT group (22.83%) compared to the continuous group (9.36%) with p<0.05. The decrease in heart rate recovery in the HIIT group (12.97%) compared to the HICT group (6.62%) with p<0.05. A decrease in the resting heart rate of the HIIT group (18.7%) compared to the HICT group (9.9%) with p<0.05. It can be concluded that HIIT method is better at increasing VO2max, decreasing heart rate recovery, and decreasing resting heart rate than the HICT method.